2017
DOI: 10.1021/acsbiomaterials.7b00344
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Near-Infrared Conjugated Polymer for Photothermal and Chemo Combination Therapy

Abstract: Amphiphilic conjugated polymer was designed and utilized as nanocarriers without further general encapsulation using PEGylated materials for photothermal therapy (PTT) and chemotherapy. These nanocarriers have maximum absorption in ideal phototherapeutic window between 800 and 850 nm and excellent photothermal conversion efficiency of 76% at 808 nm. It provides the simultaneous therapy of chemotherapy and PTT with the monitoring of photoacoustic imaging. After combined therapy via tail vein injection, complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Remarkable anticancer effect in vivo was achieved by combined chemo-photothermal therapy. Other groups also designed various nano-platforms for combined chemo-photothermal therapy by loading drugs in PPy-based nanomaterials, mainly by physical interactions (Wang Y. et al, 2014; Wang J. et al, 2015; Wang K. et al, 2016; Zhu et al, 2016; Chen X. J. et al, 2017; Yao et al, 2017). Very recently, Hu et al prepared multifunctional PPy/micelle hybrid nanoparticles (denoted as CPT@DOX-UCST/PPy) by polymerizing pyrrole in the shell of polymeric micelles with upper critical solution temperature (UCST) feature (Figure 6; Yang et al, 2018).…”
Section: Organic Nanomaterials-based Chemo-photothermal Therapymentioning
confidence: 99%
“…Remarkable anticancer effect in vivo was achieved by combined chemo-photothermal therapy. Other groups also designed various nano-platforms for combined chemo-photothermal therapy by loading drugs in PPy-based nanomaterials, mainly by physical interactions (Wang Y. et al, 2014; Wang J. et al, 2015; Wang K. et al, 2016; Zhu et al, 2016; Chen X. J. et al, 2017; Yao et al, 2017). Very recently, Hu et al prepared multifunctional PPy/micelle hybrid nanoparticles (denoted as CPT@DOX-UCST/PPy) by polymerizing pyrrole in the shell of polymeric micelles with upper critical solution temperature (UCST) feature (Figure 6; Yang et al, 2018).…”
Section: Organic Nanomaterials-based Chemo-photothermal Therapymentioning
confidence: 99%
“…The resultant nanoparticles showed strong absorption in NIR region with high PCE (≈50%), and were further employed for PA imaging guided photothermal/chemo combined therapy in mice. Li et al . designed an amphiphilic CP with pendent PEG units, where DOX was encapsulated into the self‐assembled CP without the assistance of other PEGylated materials.…”
Section: Applications Of Photothermal Cpsmentioning
confidence: 99%
“…The photoacoustic images have confirmed in vivo temperature increase of more than 20% upon laser irradiation. PAI has also been used in biodistribution studies as demonstrated by Yao et al ( Figure ) . These authors have synthesized NIR absorbing amphiphilic polymers which self‐assemble into micelles that can encapsulate chemotherapeutic drugs such as DOX.…”
Section: Imaging Advantagesmentioning
confidence: 99%
“…PAI of tumor‐bearing mice treated with DOX‐NPs after A) 2, B) 12, and C) 24 h; D) quantitative analysis results from PAI of DOX‐NPs accumulated in liver, spleen, kidney, and tumor at different times. Reproduced with permission . Copyright 2014 American Chemical Society.…”
Section: Imaging Advantagesmentioning
confidence: 99%